Burden of opioid use disorder in the Middle East and North Africa (MENA): findings from Global Burden of Disease (GBD) study - Mohammad Effatpanah; Homa Seyedmirzaei; Hossein Karami; Pegah Rasoulian; Reza Mehrizi; Khashayar Danandeh; Leila Ghamkhar; Zeynab Efatpanah; Amin Nakhostin-Ansari (Journal of Health, Population and Nutrition)
Abstract Background Opioid Use Disorders (OUDs) present critical health challenges across the Middle East and North Africa (MENA) region. The primary objective of this study is to assess the prevalence and burden of OUDs within the MENA region. Methods In the current study, we used the Global Burden of Diseases (GBD) 2019 study data. In the GBD study, OUDs were defined as the ICD-10 codes of F11.0-F11.9, P96.1, and R78.1 and the DSM-IV (Diagnostic and Statistical Manual of Mental Disorders, Fourth Edition) code of 304.00. We retrieved the prevalence, death, and disability-adjusted life year (DALY) crude rates and age-standardized rates for OUDs throughout MENA countries, the MENA area, and globally, across years (from 1990 to 2019), genders, and age groups. Results Age-standardized DALY rate of OUDs in MENA increased by 40.6%, from 104.4 (95% UI: 78.2–136.0) in 1990 to 147.0 (95% UI: 111.8-187.7) per 100,000 people in 2019. In 2019, the highest DALY rate of OUDs for both males (411.3 per 100000) and females (330.2 per 100000) and in total (372.3 per 100000) was in the 25–29 years age group. In 2019, the highest age-standardized DALY rates of OUDs were UAE (373.9 per 100000, 95% UI: 278.2-481.7), Libya (341.1 per 100000, 95% UI: 248.9-435.8), and Iran (281.5 per 100000, 95% UI: 221.1–349.0). Age-standardized DALY rates decreased in Qatar (-10.2%) and Iraq (-1.9%) from 1990 to 2019. While, age-standardized DALY rates increased in other countries, with the highest increases being in Libya (167.3%), Lebanon (121.1%), and UAE (113.31%). Conclusions The burden of OUDs has increased from 1990 to 2019 in the MENA region. These results necessitate new governmental policies and global collaborations to effectively control opioid production and trafficking and manage their negative health-related outcomes.